Knowledge, Practice, and Associated Factors of Essential Newborn Care among Sudanese Women in Eastern Sudan - Abdullah Al-Nafeesah; Mohammed Ahmed A. Ahmed; Omer Elhory; Hyder M. Mahgoub; Bahaeldin A. Hassan; Osama Al-Wutayd; Ishag Adam (MDPI AG, 2022)
(1) Background: There is a high neonatal mortality rate in countries with low resources, especially sub-Saharan countries. There is no published data in Sudan on mothers' knowledge and practice of essential newborn care. This study aimed to assess the maternal knowledge and practice of essential newborn care in Gadarif city, eastern Sudan. (2) Methods: A cross-sectional study was conducted in Gadarif city, eastern Sudan. Postnatal mothers (384) were recruited from postnatal and vaccination clinics. A structured questionnaire was used to collect the data. Mothers who responded to essential newborn care knowledge and practice items at a rate equal to 75% or above were classified as having good knowledge and practice. Logistic regression analysis was performed to identify the factors associated with essential newborn care knowledge and practice. (3) Results: In this study, 268 (66.4%) and 245 (63.8%) of the 384 participants had good knowledge and practice of essential newborn care, respectively. None of the investigated factors (age, residence, education, occupation, parity, antenatal care, and mode of delivery) was associated with knowledge and practice of essential newborn care with sociodemographic and obstetric factors. Mothers with poor knowledge were less likely to have good practices (adjusted odds ratios = 0.41; 95% CI (0.26-0.64)). The reported malpractices were giving dietary supplements to the babies (48.2%), mainly water (40.0%) and cow's milk (43.2%), and putting substances on the umbilical cord (62.8%), with butter (92.1%) accounting for the majority. (4) Conclusion: In the present study, around two-thirds of the participants had good essential newborn care knowledge and practice. Poor knowledge was less likely to be associated with good newborn care practices. More research is needed to build baseline data for neonatal mortality reduction plans.